The new international paradigm of resilience approaches in peacebuilding in the post-conflict Timor-Leste - Kaneko, Yumiko (2020)
This thesis is about the new international paradigm of resilience approaches in peacebuilding in the post-conflict Timor-Leste. In these three decades, international governance has significantly changed its focus, approaches and outcomes in order to cope with an uncertain and volatile world. There are two aims motivating this research: unfold new theoretical frameworks of global governance; and analyse the impact of prevalent resilience approaches on security systems, especially in terms of peacebuilding.